Atlantoaxial Rotatory Subluxation in Children. Issue 6 (June 2015) - Neal, Kevin M.; Mohamed, Ahmed S.
Abstract : Atlantoaxial rotatory subluxation is a rare condition in which patients present with the acute onset of torticollis. Atlantoaxial rotatory subluxation represents a spectrum of disease from muscle spasm to a fixed mechanical block to reduction of the atlantoaxial complex. If left untreated, some cases may resolve spontaneously; however, other cases may result in the development of secondary changes in the bony anatomy of the atlantoaxial joint, leading to persistent deformity. Diagnosis of the condition is largely clinical but can be aided by various imaging modalities, including radiographs, dynamic CT scanning, three-dimensional CT reconstructions, or MRI. Consideration should always be given to infection or other inflammatory disease as an underlying, precipitating cause. Treatments include observation, the use a cervical collar and analgesics, halter or skeletal traction, and posterior fusion of C1-C2. The most important factor for success of conservative treatment is the time from the onset of symptoms to recognition and the initiation of treatment.